FINANCIAL PERFORMANCE BEFORE AND AFTER THE MERGER STUDY AT INDONESIAN SYARIAH BANK - Hairani, Khadizah; Wulandari, Tri; Dewi, Nurmala; Samosir, Poppy Marlina; Purba, Dhea Rahmadani; Hasanah, Nur Qory (Proceeding International Seminar of Islamic Studies, 2024)
The aim of this research is to find out the financial performance of 3 banks, namely Bank Mandiri Syariah, BRI Syariah and BNI Syariah based on profitability before the merger and after the merger. This research is a type of qualitative descriptive research. The aim of this research is to interpret and explain data relating to the current situation, attitudes or views that occur in society, the conflict between two or more situations, the influence of a condition and so on. The merger of the three Sharia Banks was realized in February 2021 and then changed its name to BSI. With reference sources from 5 national journals and 2 international journals with databases sourced from research journal articles, namely Google Scholar, ScienceDirect, Researchgate and collecting data from sharia banking statistics published by the Financial Services Authority in the form of financial reports obtained from the official website each sharia banking. Based on the financial reports of the three Islamic banks that carried out the merger as well as the financial performance and liquidity of these banks for the last two years from 2019-2020 (Financial Performance of Indonesian Sharia Banking et al., 2022). This research uses secondary data. BSI's financial performance before and after the merger shows that it is better after the merger because a lower ratio shows the level of bank effectiveness in achieving higher profits. Based on the results of the company's financial performance analysis using financial ratios, the merger has not had a positive impact on banking. In other words, the economic motive for the merger activities of the three Sharia banks has not been achieved for the period one year before and one year after the implementation of the merger.